Barriers and catalysts in building the institutional image of a pondok pesantren - Ropita, Ropita; Nugroho, Aris Dwi; Fitriani, Suci (Indonesian Research Journal in Education |IRJE|, 2026)
This study investigates the factors influencing the institutional image of Pondok Pesantren Ar-Rahmah in Jambi by identifying both internal catalysts and barriers that shape public perception. Using a qualitative approach, data were collected through in-depth interviews and participatory observation involving pesantren leaders, teachers, and parents. The findings indicate that visionary leadership, strong support from the foundation, and continuous student achievements—particularly in religious competitions such as the Musabaqah Tilawatil Qur’an (MTQ)—serve as key catalysts in strengthening the pesantren’s image. Visionary leadership fosters discipline, academic excellence, and moral integrity, while foundation support provides institutional stability. However, the study also identifies major barriers, including limited shared understanding of strategic goals among internal stakeholders, human resource constraints in digital communication and public relations, and challenges in managing time and institutional priorities. These barriers hinder the consistent implementation of image-building strategies. The study recommends improving internal communication, enhancing digital competencies, and strengthening priority management to sustain a positive institutional image.